X‐ray focal spot reconstruction by circular penumbra analysis—Application to digital radiography systems. Issue 1 (28th December 2015) - Di Domenico, Giovanni; Cardarelli, Paolo; Contillo, Adriano; Taibi, Angelo; Gambaccini, Mauro
Abstract : Purpose: The quality of a radiography system is affected by several factors, a major one being the focal spot size of the x‐ray tube. In fact, the measurement of such size is recognized to be of primary importance during acceptance tests and image quality evaluations of clinical radiography systems. The most common device providing an image of the focal spot emission distribution is a pin‐hole camera, which requires a high tube loading in order to produce a measurable signal. This work introduces an alternative technique to obtain an image of the focal spot, through the processing of a single radiograph of a simple test object, acquired with a suitable magnification. Methods: The radiograph of a magnified sharp edge is a well‐established method to evaluate the extension of the focal spot profile along the direction perpendicular to the edge. From a single radiograph of a circular x‐ray absorber, it is possible to extract simultaneously the radial profiles of several sharp edges with different orientations. The authors propose a technique that allows to obtain an image of the focal spot through the processing of these radial profiles by means of a pseudo‐CT reconstruction technique. In order to validate this technique, the reconstruction has been applied to the simulated radiographs of an ideal disk‐shaped absorber, generated by various simulated focal spot distributions. Furthermore, the method has been applied to the focal spot of a commercially available mammography unit. Results: In the case of simulated radiographs, the results of the reconstructions have been compared to the original distributions, showing an excellent agreement for what regards both the overall distribution and the full width at half maximum measurements. In the case of the experimental test, the method allowed to obtain images of the focal spot that have been compared with the results obtained through standard techniques, namely, pin‐hole camera and slit camera. Conclusions: The method was proven to be effective for simulated images and the results of the experimental test suggest that it could be considered as an alternative technique for focal spot distribution evaluation. The method offers the possibility to measure the actual focal spot size and emission distribution at the same exposure conditions as clinical routine, avoiding high tube loading as in the case of the pin‐hole imaging technique.